Association between serum uric acid concentration and radiographic axial spondylarthritis: a cross-sectional study of 202 patients - Lai, Yupeng; Zhang, Yanpeng; Lei, Zhihao; Huang, Yihong; Ni, Tongxin; He, Pin; Li, Xiaoling; Xu, Chiduo; Xia, Jun; Wang, Meiying (Chinese medical journal, 2023)
Furthermore, it has been reported that gout could mimic SpA. [...]our study explored whether the development of radiographic axial SpA is related to high SUA concentration. The unit of measurement for uric acid was μmol/L, which was relatively small for observing changes. [...]we transformed the unit of measurement for uric acid from μmol/L into 10 μmol/L, after collecting the raw data on uric acid levels. No significant difference was found between the radiographic group and the non-radiographic group with respect to age, gout, peripheral involvement, enthesitis, dactylitis, uveitis, psoriasis, inflammatory bowel disease (IBD), erythrocyte sedimentation rate (ESR), CRP, creatinine, BASFI, and NSAID usage. According to the previous report about MSU deposition at sacroiliac joints and our discovery about the relationship between SUA and radiographic axial SpA, we found that SUA was another possible factor for sacroiliitis progression.